Neuroeducation in Moroccan Secondary Schools: Teachers’ Perceptions, Practices, and Challenges in Life and Earth Sciences - Lafdi, Salma; Essedaoui, Aafaf; Kouchou, Ihsane; Selmaoui, Sabah (European Scientific Journal, ESJ, 2026)
Neuroeducation, at the intersection of neuroscience, cognitive psychology, and pedagogy, offers brain-based approaches to optimize learning conditions by strengthening learners’ attention, memory, and motivation. In Morocco, despite efforts to improve the quality of teaching and learner achievement in various scientific disciplines, numerous studies show that major difficulties persist, namely cognitive obstacles such as limited abstract thinking skills and problems with attention and memory. Faced with this situation, research shows that knowledge from the neuroscience of learning can inform concrete pedagogical choices, helping teachers understand how attention, memory, and motivation work, and transforming the way teaching sequences are organized to better take into account the diversity of profiles. In this context, this study aims to examine Moroccan life and earth science teachers’ perceptions, current practices, and the challenges they face in implementing neuroeducational strategies. A quantitative survey was conducted with 71 secondary school teachers in the Marrakech-Safi and Casablanca-Settat regions. Data were collected using a validated questionnaire. The results indicate a generally positive perception, with 81% of participants recognizing the effectiveness of neuroeducational techniques. However, effective implementation remains limited by structural constraints such as overcrowded classrooms and a lack of specific training. While providing original insights into the Moroccan context, the study is limited by its sample size and the declarative nature of the data. These findings highlight the urgent need for integrating neuroeducation into teacher training programs to bridge the gap between theoretical knowledge and classroom application.